Contexts of Radicalization of Jihadi Foreign Fighters from Europe - Eylem Kanol (Perspectives on Terrorism, 2022)
The research for this article is based on original biographical and relational data on 1,019 foreign fighters from France, Germany, and the UK who had traveled to a conflict country due to their Jihadi convictions between the years 2000 and 2016. It investigates where and how they had radicalized. The findings suggest that foreign fighters were primarily recruited through interpersonal or religious organizational networks. Salafist mosques, radical religious associations, and more informal groups dedicated to proselytizing were particularly crucial to the radicalization process. In contrast, contexts such as the Internet or prisons were comparably less relevant to the radicalization process of foreign fighters. The important role of interpersonal and organizational ties was further evidenced by social network analysis, which found that the majority of foreign fighters were linked within a single social network prior to their mobilization. Overall, the findings document the continued relevance of religious organizations in the recruitment and mobilization of jihadi foreign fighters.
Keywords: 330; foreign fighters; ISIS; al-Qaeda; radicalization; jihad; social network analysis